2021
DOI: 10.47197/retos.v42i0.88052
|View full text |Cite
|
Sign up to set email alerts
|

The effect of balanced versus unbalanced football small-sided games on decision-making in youth football players (El efecto de los juegos reducidos de fútbol equilibrado versus desequilibrado en la toma de decisiones de los jugadores de fútbol Juvenil (Th

Abstract: Decision-making (DM) is an important ability targeted in the formation of young football players that can improve by using small-sided games (SSGs). The main purpose of this study was to assess players’ DM in different balanced and unbalanced SSG formats keeping the play area constant. The sample was composed of 10 field players plus 2 goalkeepers (13.55±0.51 years). This study consisted of 3 sessions, one day for each session, with an interval of 48 hours apart between sessions. Three different SSG formats (4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
(22 reference statements)
0
1
0
Order By: Relevance
“…One of the things you can do to get rid of boredom is to practice playing soccer, namely 3v3 and 4v4. Several previous studies have revealed that the use of the SSG (small side games) format with an unequal number of players (4v5, 5v6) in training can be beneficial for the development of DM (decisionmaking), and therefore can be an important factor to consider in the formation of soccer players young (Sousa et al, 2021). Small sided games are a suitable training tool or method for improving technique.…”
Section: Introductionmentioning
confidence: 99%
“…One of the things you can do to get rid of boredom is to practice playing soccer, namely 3v3 and 4v4. Several previous studies have revealed that the use of the SSG (small side games) format with an unequal number of players (4v5, 5v6) in training can be beneficial for the development of DM (decisionmaking), and therefore can be an important factor to consider in the formation of soccer players young (Sousa et al, 2021). Small sided games are a suitable training tool or method for improving technique.…”
Section: Introductionmentioning
confidence: 99%
“…In adversary or collective sports, such as football, RT is a key component of performance, as players are required to make quick decisions to be successful in their actions (Sousa et al, 2021;Ruschel et al, 2011;Mudric et al, 2015;van de Water et al, 2017).…”
Section: Introductionmentioning
confidence: 99%